Jobs Impact of Green Energy - Kim, Jaden (IMF Working Papers; Working Paper ;, 2022)
This brief paper accompanies the Green Energy and Jobs tool, which is a simple excel-based tool to estimate the job-creation potential of greening the electricity sector. Specifically, it calculates the net job gains or losses from increasing the level of energy efficiency, and from increasing the share of clean and renewable electricity generation in the total electricity output mix. The tool relies on estimates of job multipliers in the literature, and adds evidence from firm-level data on the job-intensity of different energy sources. The paper illustrates applications of the tool using data from the IEA's Sustainable Development Scenario compared to business-as-usual. This tool is intended to help country teams engage further on climate change issues in bilateral surveillance.